Chronic Stress Disturbs Metabolome of Blood Plasma and Urine in Diabetic Rats - Ren, Yu; Yang, Cheng-hua; Li, Zhu-man; Yang, Zhen; Xiao, Zhi-jun; Duan, Jing-jing; Zhou, Ting; Xu, Feng (Frontiers in Psychiatry, 2018)
About 30% of diabetes patients suffer from varying degrees of depression. Diabetes itself is associated with abnormal carbohydrate and energy metabolism. Whether chronic stress-induced depression-like behavior impacts the metabolome of blood plasma and urine in diabetes is not clear. This study aimed to investigate the effect of chronic stress on metabolome of plasma and urine in spontaneously diabetic GK rats. The GK rats were subjected to chronic unpredictable mild stress (CUMS) in 8 weeks to induce depression-like behavior. We performed metabolome analysis of blood plasma and urine using liquid chromatography mass spectrometry (LC/MS). Multivariate data analysis was used to evaluate the data. Behavior and biochemical assay confirmed the successful establishment of CUMS-induced depression-like behavior model in rats. At the end of model establishment, disturbance of 20 plasma metabolites and 16 urine metabolites were detected in CUMS-induced depression GK rats as compared to control rats. These disturbed metabolites were involved in fatty acid metabolism, sphingolipid metabolism, phenylalanine metabolism, citrate cycle, glycolysis, glutathione metabolism, and nicotinate and nicotinamide metabolism. This study suggest that chronic stress-induced depression-like behavior may further disturb diabetes-itself energy metabolome. The plasma and urine lipid metabolites monitoring may be useful for early detection of depression in patients with diabetes mellitus.